2008
DOI: 10.1016/j.neuroscience.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol replacement modifies c-fos expression at the spinomedullary junction evoked by temporomandibular joint stimulation in ovariectomized female rats

Abstract: The influence of estradiol (E2) treatment on temporomandibular joint (TMJ) nociceptive processing in the caudal trigeminal sensory brain stem complex was assessed in ovariectomized female rats by quantitative Fos-immunoreactivity (Fos-LI). After 2 days of daily injections of high (HE2) or low (LE2) dose E2 rats were anesthetized and the small fiber excitant, mustard oil (MO, 0-20%), was injected into the TMJ and after two hours later brains were processed for Fos-LI. TMJ-evoked Fos-LI in laminae I-II at the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 78 publications
3
23
1
Order By: Relevance
“…This pattern of Fos expression was consistent with earlier results (Bereiter 2001; Okamoto et al 2008) and confirmed that the low dose E2 regimen used here was not sufficient to enhance TMJ-evoked Fos-LI in the TBNC. Analyses of TMJ-evoked Fos-LI within individual brainstem regions found only minor sex differences (Tables 1, 2 and 3).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This pattern of Fos expression was consistent with earlier results (Bereiter 2001; Okamoto et al 2008) and confirmed that the low dose E2 regimen used here was not sufficient to enhance TMJ-evoked Fos-LI in the TBNC. Analyses of TMJ-evoked Fos-LI within individual brainstem regions found only minor sex differences (Tables 1, 2 and 3).…”
Section: Resultssupporting
confidence: 93%
“…Sensory afferent nerves that supply the TMJ and muscles of mastication terminate at multiple rostrocaudal levels of the trigeminal brainstem nuclear complex (TBNC) and upper cervical dorsal horn (Shigenaga et al 1988; Dessem et al 2007). C-fos immunohistochemical studies have confirmed that select regions of the TBNC that receive direct input from the TMJ, e.g., dorsal paratrigeminal region (dPa5) and superficial laminae of Vc and upper cervical dorsal horn (C 1–2 ), encode the intensity of an intra-TMJ stimulus in an estrogen-dependent manner (Bereiter 2001; Okamoto et al 2008). Anatomical tract-tracing combined with c-fos methods have been used to report that TBNC neurons responsive to jaw muscle (Ikeda et al 2003; Sugiyo et al 2005) or TMJ injury (Yamazaki et al 2008) projected to higher brain centers associated with nociceptive processing; however, only male animals were included in these studies.…”
mentioning
confidence: 95%
“…Evidence shows that estrogen can sensitize TMJ nociception through central trigeminal ganglion. 5,48,64 Consistently, both our Figure 3. Attenuation of mechanical allodynia of inflamed TMJ by blocking NGF in the hippocampus.…”
Section: Central Mechanism Underlying Modulation Of Gender-based Diffsupporting
confidence: 83%
“…49 Many studies have been done to understand how estrogen affects peripheral and central nociceptive processes related to TMJ inflammatory pain. 5,15,24,25,47,48,64,70 However, whether estrogen enhances or decreases TMJ nociception remains controversial among these studies. Evidence shows that estrogen can sensitize TMJ nociception through central trigeminal ganglion.…”
Section: Central Mechanism Underlying Modulation Of Gender-based Diffmentioning
confidence: 99%
“…The main features of the disease are the damage and loss of the articular cartilage tissue 1) . There are two kinds of treatment methods for TMJOA.…”
Section: Introductionmentioning
confidence: 99%